Parallelization of iterative and direct schemes for Keller-Box method on distributed memory platform - Alias, Norma; Hamzah, Norhafizah; Saidina Amin, Norsarahaida; Darwis, Roziha; Satam, Noriza; A. Ghaffar, Zarith Safiza (2010)
In this paper, we present iterative schemes, specifically the conjugate gradient, and Gauss seidel red-black (GSRB) and direct schemes namely LU factorization and Gauss elimination for Keller-box scheme. The aim of this paper is to offer reasonable assessments and contrasts on behalf of the numerical experiments of these two schemes ported to run through Parallel Virtual Machine (PVM) on distributed memory platform. The computational complexity also presented for the comparison purpose, and the graphs of parallel evaluation in terms of speedup, efficiency, effectiveness and temporal performance are presented as well.